The Food and Agriculture Organisation of the United Nations: A Systems Analysis - Miller, John Anthony (My University, 1966)
A selective case study of the Food and Agriculture Organisation (F.A.O.) in terms of a concept of the political system.
Keywords: Political Science; Political Science